Low-level red-light therapy as a novel modality for myopia control in children: A systematic review - Dewi, Arlin Chyntia; Budihardja, Brigitta Marcia; Jutamulia, Jovita (Paediatrica Indonesiana, 2024)
Background Due to the COVID-19 pandemic causing a rise in digital technology use, online e-learning, and decreased outdoor time, the prevalence of myopia is expected to increase. Therefore, finding an effective strategy for myopia progression control is of high importance. Low-level red-light therapy (LLRT) has been proposed as a new modality in myopia progression control. Objective To assess the efficacy of LLRT for myopia control in children. Methods A comprehensive literature search of four online databases (PubMed, Cochrane, ProQuest, and WorldCat) was performed. We included original studies that assessed the efficacy of LLRT for myopia control in children and excluded animal studies, case reports, articles with no full-text available, and articles not in English. Risk of bias assessment was performed using different tools according to the study type. The main outcome measurements were changes in axial length (AL) and spherical equivalent refraction (SER). Results Three clinical studies, two randomized controlled trials and one retrospective cohort study, were reviewed. A total of 296 children in the treatment group were evaluated. Children using single-vision spectacle only or orthokeratology lenses were evaluated for comparison. All studies had reported significantly improved outcomes, with lower mean AL changes and greater SER improvement in the LLRT group compared to the control group (P<0.001 in all studies). Conclusion Although studies on LLRT are still limited, the treatment has shown promising results for myopia control in children. More studies to evaluate the efficacy of this new strategy are needed.